2021
DOI: 10.1002/cjce.24251
|View full text |Cite
|
Sign up to set email alerts
|

A modified acid system to enhance carbonate matrix acid stimulation: An experimental study

Abstract: In carbonate matrix acidizing, the critical design parameters are interstitial velocity and pore volume to breakthrough for wormhole propagation (vi, opt and PVBT,opt). Hydrochloric acid (HCl), the most commonly used acid in carbonate acidizing, sometimes shows low efficiency because the injection rate needed for optimal wormhole propagation is not attainable, especially for when long completion intervals, low permeability carbonates, or coiled tubing operations are involved. It also raises safety, corrosion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Efficient wormhole creation into low permeability carbonate systems is a well-recognized challenge due to the fast rection rate between HCl and calcium carbonate. , The rapid neutralization of the acid spearhead in these high carbonate samples suggests that the acid spearhead may be useful for initiating fractures in extremely calcite-rich rocks but does little to enhance rock porosity. If 100% of the acid spearhead is assumed to be neutralized by calcite, 90–99% of the total calcite remains unreacted (see Table S7 for calculations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient wormhole creation into low permeability carbonate systems is a well-recognized challenge due to the fast rection rate between HCl and calcium carbonate. , The rapid neutralization of the acid spearhead in these high carbonate samples suggests that the acid spearhead may be useful for initiating fractures in extremely calcite-rich rocks but does little to enhance rock porosity. If 100% of the acid spearhead is assumed to be neutralized by calcite, 90–99% of the total calcite remains unreacted (see Table S7 for calculations).…”
Section: Discussionmentioning
confidence: 99%
“…Dissolution of carbonates ( e.g. , calcite and dolomite) in shales due to the injection of acid, most commonly HCl, has been shown to increase porosity and open pore throats in the shale matrix. ,, This is particularly crucial for carbonate-rich systems. Lu et al observed a limited increase in the permeability of Eagle Ford shale (52 wt % calcite) pre- and post-exposure to NaCl brine; however, Marcellus shale (6 wt % calcite, 3 wt % dolomite) exposed to the same brine showed a 5 times increase in permeability, which was assumed to be due to differences in mineral dissolution that either limited or enhanced further penetration of the fluid for the Eagle Ford and Marcellus shales, respectively. Li et al compared the chemically altered zone of a carbonate-poor Marcellus shale (1 wt % calcite, 6 wt % dolomite) and a carbonate-rich Eagle Ford shale (52 wt % calcite) exposed to HFF and quantified that carbonate dissolution extended deeper into the carbonate-poor matrix compared to the carbonate-rich matrix (100–200 vs 30–40 μm, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the shorter residence time of the acid in the formation, especially at high temperatures, the wormholes created are less efficient hydrocarbon channels (Chacon and Pournik, 2022). Therefore, gelled acid, foamed acid, micro-emulsified acids, and other chemical agents have been formulated in an effort to circumvent the drawbacks of the fast acid-rock reaction by lowering H + ion dissociation, reducing H+ ion mass transfer, and changing the wettability of the rock surface (Zhu et al, 2022).…”
Section: Importance Of Matrix Acidizing For Tight Carbonate Reservoirsmentioning
confidence: 99%
“…The Canadian Journal of Chemical Engineering is acknowledged for dedicating this special issue to the living memory of Dr. Nasr‐El‐Din. This acknowledgment is also extended to the authors who contributed to this special issue [ 1–28 ] as well as the guest editors:…”
mentioning
confidence: 99%